(untitled) (Research, Society and Development, 2025)
The intensification of interaction between humans and animals over time has become a significant concern for public health, as well as for preventive and community veterinary medicine. Considering that rabies is a viral zoonosis of high epidemiological relevance, with a predilection for mammals, both domestic and wild, characterized by an acute, progressive, and often fatal clinical course, it is essential to promote awareness among those responsible for domestic animals regarding prophylactic measures and the necessary care for the prevention of the disease. This study aimed to investigate the understanding of the population of Cacoal-Rondônia regarding rabies, seeking to gather information about the population’s basic knowledge about the disease. One hundred people aged between 18 and 57 years were interviewed; all of them owned animals in their homes. Regarding rabies being a serious disease, 100% said yes, however, 6% do not vaccinate their animals. 92.7% answered correctly that all mammals are capable of transmitting rabies, and 88.1% that the causative agent is a virus. This study revealed that people with lower levels of education have less knowledge about this zoonosis.